FPGA IMPLEMENTATION OF ZIEGLER-NICHOLS CLOSED-LOOP METHOD FOR AUTOMATIC PID PARAMETERS TUNING - Nurotul Auliya'; Nanang Sulistiyanto; Mohamad Hairol Bin Jabbar (Jurnal Mahasiswa TEUB, 2015)
A control loop is necessary in order to control a plant or system in order to gain low error system, robust system, or system with fast response depend on the purpose. The most commonly known and used control loop is Proportional-Integral/Proportional-Integral-Derivative. In order to gain the desired output, its parameters, which have different effects, have to be set according to the design requirements. Several methods can be used to determine the parameter; one of them is Ziegler-Nichols closed-loop method. The purpose of this project is to carry out FPGA implementation of Ziegler-Nichols closed-loop method for automatic PID parameters tuning. The commonly used design hardware for digital projects is microcontroller. Microcontroller device resources is limited, we do not know how much device resources this project will take, and to add an additional resources is quite complicated as well, therefore we choose FPGA instead. This project is part of a bigger project which consists of three projects, which are handled by a student each. The most important parts for this project are estimator and controller modules which are located in the FPGA. This is because the estimator’s function is to do the steps of the Ziegler-Nichols closed loop method and the controller is necessary because the estimator cannot function if there is no controller. To build and test out the system, it is necessary to begin from the subsystems. If the subsystem’s tests are successful, then the probability for the overall system to be success is higher. Experimental results show that the subsystems have been successfully designed, but the overall system could not be applied because the target Spartan 3E FPGA does not have sufficient logic resources on. The first and second objectives was achieved but the third objective was not achieved because this project could not be applied on the target FPGA and therefore this project has not been used on the real tools.Keywords – Auto-tuning PID controller, Ziegler-Nichols, FPGA Implementation